Transforming M&E for Uncertain and Complex Contexts: The UNDP’s Innova tion Sandbox Approach - Fraser, Dugan; Haldrup, Søren (2022)
How can we transform monitoring and evaluation (M&E) into a more adapt ive, emergent process to address uncertainty and complexity in todays’ world? How do we move from compliance and accountability to learning – to support better, more timely, decisions? Join GEI Program Manager, Dugan Fraser, as he discusses these questions and others with Special Guest, Søren Haldrup, from UNDP's Strategic Innovation Unit where he manages UNDP's innovation facility and leads a new initiative called t he M&E Sandbox.